Role of Non-invasive Preimplantation Genetic Testing-Aneuploidy Using Spent Culture Media and its Concordance with Trophectoderm Biopsy: A Proof of Concept and Validation Study - Neeta Singh; Ankita Sethi; Lata Rani; Monika Saini; Ritu Gupta; Neena Malhotra; Reeta Mahey (Journal of Human Reproductive Sciences)
Background: While trophectoderm (TE) biopsy with next-generation sequencing (NGS) remains the gold standard for preimplantation genetic testing for aneuploidy (PGT-A), the discovery of cell-free DNA (cfDNA) in spent culture media (SCM) has sparked interest in non-invasive PGT-A (NiPGT-A) as a potential alternative. Aim: The study was conducted to assess the feasibility of cell cfDNA from SCM as a tool for NiPGT-A in patients undergoing IVF for advanced age, repeated implantation failure or severe male factor infertility. Settings and Design: This is a prospective study where a total of 44 embryos having TE biopsy for aneuploidy testing and their respective SCM collected at day 5/6 were analysed. Materials and Methods: All aneuploid blastocysts (WB) were subjected to DNA extraction and amplification using Sureplex DNA amplification system followed by library preparation using VeriSeq™ PGS Library Prep kit and sequencing on MiSeq (Illumina, California, USA). Statistical Analysis Used: Copy Number Variation visualisation and analysis were carried out using BlueFuse Multi Software (Illumina). The statistical data were analysed by STATA version 14. Results: Informative results were obtained in 36/44 (81.2%) SCM samples. The reads were analysable in 26 paired (SCM and TE biopsy) samples. Concordant NGS results for both TE biopsy and SCM sample were obtained in 17/26 (65.38%) embryos. The per chromosome concordance rate was 85.13% (487/572) and the sex chromosome concordance rate was 73% (19/26). The sensitivity and specificity of NiPGT-A were 66.6% and 60%, respectively. On comparing the ploidy concordance rate, poor morphology embryos had better, but not statistically significant concordance rate (83.33%) as compared to good morphology embryos (50%, P = 0.16). Although not significant, day 6 embryos had better per chromosome as well as sex chromosome concordance rate as compared to day 5 embryos. Conclusion: Aneuploidy testing using cf DNA in SCM is a promising technique but needs more research on larger cohort size to improve the sensitivity, specificity and concordance rate.